Risk-based multi-hazard microzonation for earthquakes and tsunamis - Goda, Katsuichiro; Catalan, Patricio A. (Frontiers in Earth Science, 2025)
A multi-hazard spatial mapping for shaking and tsunami risks is necessary for coastal communities that face imminent dangers from megathrust subduction earthquakes. Conventional single-hazard (seismic or tsunami) mapping methods are not effective in addressing this research gap because the individual hazard effects cannot be combined directly. This study presents a new risk-based multi-hazard microzonation method, which displays relative risks of a representative building asset due to earthquakes and tsunamis within a local community and applies it to the District of Tofino in British Columbia, Canada, which is located in the Cascadia subduction zone. A recently developed catastrophe model is used to generate a comprehensive set of multi-hazard loss data for Tofino by reflecting two local factors, i.e., site amplification proxy for shaking and high-resolution topography for tsunami. The risk-based multi-hazard microzonation maps capture spatially varying loss contributions from shaking and tsunami hazards at different annual probability of exceedance levels. Different visualization approaches can be considered to facilitate the disaster risk management and risk communications with residents and stakeholders.